Service Characteristics Model to Make Optimum Services in Investment Department and One-Stop Integrated Service of Ciamis Regency - Wasdi Wasdi; Benyamin Harits; Lia Muliawaty (Pasundan Social Science Development, 2021)
Service Characteristic Model to Achieve Excellent Service in Investment and One-Stop Service (IOSS) of Ciamis Regency. The problem is the lack of licensing services caused by the lack of adequate service dimensions, so the licensing service is still in the red zone. At the same time, the focus is the implementation of licensing services IOSS environment in Ciamis Regency. This research uses a qualitative approach with case study method observation. The data collection technique is done by digging data derived from primary data and secondary data. Primary data were obtained through observation, interview, observation of informant behavior, and Focus Group Discussion. While the secondary data obtained from various documents, journals, scientific papers, and others. Excellent service model in IOSS of Ciamis Regency from 10 dimensions according to V. Gaspersz theory eight dimensions are still low: the dimension of timeliness, service accuracy, responsibility, completeness, convenience model variation, personal service, and comfort. Only the dimensions of modesty and hospitality are seen enough. While the dimensions of supporting attributes by the informants are considered sufficient despite the facts in the field, they have not been adequate. The research finds several things: (1) there are other dimensions beyond the ten dimensions of Gaspersz, namely the participation of the applicant's private community; (2) excellent service in IOSS of Ciamis Regency need to develop a variation of the model, from offline to semi online; (3) there are factors that are nearly the excellent service, such as the quality and quantity of human resources as well as the local revenue target burden.